2011
DOI: 10.1007/s00034-011-9309-6
|View full text |Cite
|
Sign up to set email alerts
|

Design and Analysis of Frequency-Tunable Amplifiers using Varactor Diode Topologies

Abstract: The design of frequency-tunable amplifiers is investigated and the tradeoff between linearity, efficiency and tunability is revealed. Several tunable amplifiers using various varactor diode topologies as tunable devices are designed by using loadpull techniques and their performances are compared. The amplifier using anti-series distortion-free varactor stack topology achieves 38% power added efficiency and it may be tuned from 1.74 to 2.36 GHz (about 35% tunable range). The amplifier using anti-series/anti-pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…4 (a) and (b) respectively. Also its element values are given in TABLE II which are computed by using (1) and (2). Furthermore, TPG simulation and measurement results are compared in Fig.…”
Section: B Design Of Impedance Transforming Filter Using Microstripsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 (a) and (b) respectively. Also its element values are given in TABLE II which are computed by using (1) and (2). Furthermore, TPG simulation and measurement results are compared in Fig.…”
Section: B Design Of Impedance Transforming Filter Using Microstripsmentioning
confidence: 99%
“…The design of broadband, programmable and tunable radio frequency (RF) front-end components carries extreme importance for the realization of a high frequency SDR terminal. Previous works, such as [2]- [5], have shown that tunable filters and amplifiers which are appropriate to SDR's can be designed by using different approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The objective of SDR technology is to realize reconfigurable radios that may be used for various communication systems without the need of modifying or replacing any hardware components [1]. The design of programmable and tunable radio frequency (RF) front-end components carries extreme importance for the realization of a high frequency SDR terminal.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, varactor diodes were explored to achieve continuous frequency tuning in LNAs. In [8,9] varactor diodes were implemented in the output stage of LNA to achieve reconfiguration. However, the frequency tuning range in both circuits was limited to 500 MHz.…”
mentioning
confidence: 99%